The Development and Validation of the Heterosexism Erasure Scale. (January 2023) - Shin, Richard Q.; Keum, Brian TaeHyuk; Smith, Lance C.; Lu, Yun; Yee, Stephanie
The heterosexism erasure construct captures attitudes, which deny or minimize the systemic oppression of lesbian, gay, bisexual, and queer (LGBQ) persons in the United States. Heterosexism erasure expands the interrogation of denying or minimizing discrimination (Neville at al., 2006) beyond the realm of White supremacy and into the domain of heteronormativity. The purpose of this project was to develop a psychometrically sound measure of heterosexism erasure. Two independent samples were gathered to conduct exploratory ( n = 425) and confirmatory ( n = 367) factor analyses to assess for initial reliability and validity evidence of the Heterosexism Erasure Scale (HES). Results suggest that the final 13-item HES provides a general index of heterosexism erasure as well as assesses two related, but distinct factors named Heterosexism Denial and Heterosexism Minimization. Results support the internal consistency and factor structure of the measure. Expected relationships between the HES and existing measures provide validity evidence for the instrument.